Hubungan Antara Minat Belajar dengan Prestasi Belajar Siswa pada Mata Pelajaran PAI Kelas X di SMK IT Bina Adzkia Depok - Chodidjah Makarim, Chodidjah Makarim; Ade Fitri Kurniasih, Ade Fitri Kurniasih; Noor Isna Alfaien, Noor Isna Alfaien (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this research namely: (1) to determine students' learning interest in class X PAI subjects at SMK IT Bina Adzkia Depok, (2) to determine student learning achievement in class X PAI subjects at SMK IT Bina Adzkia Depok, (3) to find out whether there is a relationship between learning interest and student learning achievement in class X PAI subjects at SMK IT Bina Adzkia Depok. The data collection technique used is a questionnaire by distributing data to 40 grade X students, for data analysis, namely scoring, normality test and homogeneity test and the method used is correlation. The results of this study show that: (1) student learning interest in PAI subjects is included in the medium category, (2) student learning achievement in PAI subjects is included in the medium category, (3) there is a positive and significant relationship between interest in learning and student learning achievement in PAI subjects which are included in the medium category.